The advertising handbook - Brierley, Sean. (London : Routledge, 2001)
The Advertising Handbook examines the reasons why companies and organizations advertise; how they research their markets; where they advertise and in which media; the principles and techniques of persuasion and their effectiveness, and how companies measure their success.
Previous ed.: 1995.
Includes bibliographical references and index.
Keywords: Business; Advertising